Analisis Yuridis Pelaksanaan Kewenangan Bawaslu sebagai Lembaga Pengawas dan Lembaga Pemutus Sengketa Pemilihan Umum - Juhardin, Juhardin; Ismail Ananda, Adhe (LP3M, Universitas Muhammadiyah Kendari, 2023)
This study aims to analyze the implementation of the authority of the Bawaslu as an election supervisory institution and election process dispute resolution. This research is a normative legal research by examining all laws and regulations related to the legal issues being studied. The research approach uses a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials, namely legal materials that are authoritative in nature, which consist of statutory regulations, official records, or treatises in making statutory regulations as well as secondary legal materials (materials that provide explanations regarding primary legal materials, including , documents, books, magazines, legal journals and research reports related to this research). The conclusion of this research has been obtained that First, Bawaslu as an election supervisory institution performs the function of preventing violations. Second, the Authority to Resolve Election Process Disputes of the Bawaslu is an attributive authority based on Law no. 7 of 2017 concerning General Elections in Article 94 paragraph (3) point d and Bawaslu Members have met the criteria as judges at the Bawaslu Adjudication Session because they have gone through such a strict selection process in accordance with the stages they have carried out and the Selection Team has conducted an assessment based on the criteria contained in article 117 of the Election Law. Third, Article 469 which states that the Bawaslu decision is final and binding is a sentence that gives position or power to the Bawaslu adjudication decision which is final. However, this power is immediately removed in the next phrase which gives exceptions to certain circumstances.